Twelfth Night - Shakespeare, William; Modernised by Alan Durband (Great Clarendon Oxford University Press, 2014)
The Shakespeare Made Easy series aims to take the fear out of Shakespeare. By having Shakespearean and Modern English facing each other, pupils will find it easier to comprehend the text. Through discussion of the life, work and theatre of Shakespeare pupils can gain a more rounded understanding of these classic works.